PERCEIVED ORGANIZATIONAL SUPPORT AND ORGANIZATIONAL COMMITMENT OF GENERATION Z EMPLOYEES: JOB SATISFACTION AS A MEDIATOR - Nurin Nadhira Alyani; Nina Siti Salmaniah Siregar; Suryani Hardjo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The ability of Generation Z employees to multitask and adjust to the newest technological advancements brings about improvements for firms that employ them. However, generation Z is perceived to be readily distracted by alternative work prospects and to seek rapid gratification, which makes them less likely to be committed to organizations. Perceived organizational support is one of the factors that predict organizational commitment. However, prior research has not explained how perceived organizational support influences organizational commitment. This correlational quantitative research aims to explain the role of job satisfaction in influencing perceived organizational support on organizational commitment among Generation Z employees. This study involved 366 participants characterized as permanent employees belonging to Generation Z working in the area of ​​District X, Medan. The research instruments use the perceived organizational support scale, the organizational commitment scale, and the job satisfaction scale, all of which have been tested for validity and reliability. The results of the SEM test indicate that job satisfaction acts as a mediator in the relationship between perceived organizational support and organizational commitment.